Characterization and inter-strain variability in ichthyotoxicity of Heterocapsa ovata (Peridiniales, Dinophyceae) from temperate waters of South Australia - Verma, Arjun; Gaiani, Greta; Hoppenrath, Mona; Dorantes-Aranda, Juan Jose; Smith, Kirsty; Kohli, Gurjeet Singh; Wilkinson, Clinton; Hallegraeff, Gustaaf Marinus; Murray, Shauna Ann (Frontiers in Protistology, 2024)
Harmful algal bloom (HAB) forming species and populations exhibit substantial intraspecific functional trait variation which can serve eco-evolutionary advantages. Phenotypic variability amongst populations can buffer immediate detrimental effects of environmental fluctuations, with more diverse populations expected to survive changing conditions more efficiently than their uniform counterparts. In February 2014, in the temperate waters of Coffin Bay, South Australia, a mixed fish-killing dinoflagellate bloom occurred, which caused the death of oysters and fish present in the area. The bloom was dominated by Karenia mikimotoi but with a cryptic species of Heterocapsa also present. Heterocapsa species, such as H. circularisquama have been associated with large-scale mortalities of bivalves and have known to cause considerable damage to aquaculture industries but have rarely been reported from Australian waters. In this study, twenty-one monoclonal Heterocapsa isolates were established from the site which were subsequently identified as H. ovata using microscopy and universal ribosomal markers (ITS/5.8S and LSU D1/D3 rDNA regions; SSU and cob were used for amplicon sequencing).They were tested for ichthyotoxicity with a bioassay based on cells from the gills of rainbow trout (Oncorhynchus mykiss). Culture fractions preparations (whole cells, supernatant and lysed cells) were analysed with the highest ichthyotoxicity observed in lysed cells but with surprisingly high inter-strain variability. Results from this study expand our understanding of adaptation, and also enable us to predict the dynamics of future populations under changing climatic regimes.